The relationship between teacher care behavior and English learning performance: a serial multiple mediation model - Wang, Dongmei; Wu, Qiusheng; Lei, Cong (Frontiers in Psychology, 2025)
This study explores the link between Teacher Care Behavior (TCB) and English Learning Performance (ELP), examining a serial multiple mediation of English Learning Motivation (ELM), English learning Engagement (ELE), English Self-efficacy (ESE), and English learning Strategies (ELS). A questionnaire survey assessed these factors, with ELP based on CET-4 (College English test-band 4) scores. The serial multiple mediation model revealed TCB positively predicts ELP through two motivational-cognitive chains based on Self-Determination Theory (SDT) and Social Cognitive Theory (SCT). The SDT-driven motivational pathway is TCB → ELM→ELE → ELP and SCT-driven cognitive-efficacy pathway is TCB → ESE → ELS → ELP. These findings offer new insights into TCB and student psychological mechanisms in foreign language (FL) learning, providing a theoretical and practical basis for optimizing the learning environment and enhancing outcomes.